Astilbin prevents osteoarthritis development through the TLR4/MD‐2 pathway. Issue 22 (16th October 2020) - Sun, Shuaibo; Yan, Zijian; Shui, Xiaolong; Qi, Weihui; Chen, Yanlin; Xu, Xinxian; Hu, Yuezheng; Guo, Weijun; Shang, Ping
Abstract: Osteoarthritis has become one of the main diseases affecting the life of many elderly people with high incidence of disability, and local chronic inflammation in the joint cavity is the most crucial pathological feature of osteoarthritis. Astilbin is the main active component in a variety of natural plants such as Hypericum perforatum and Sarcandra glabra, which possess antioxidant and anti‐inflammatory effects. At present, there is no study about the protective effect of Astilbin for osteoarthritis. The purpose of this study was to investigate the effect of Astilbin in human OA chondrocytes and mouse OA model, which was established by surgery‐mediated destabilization of the medial meniscus (DMM). In vitro, we found that Astilbin pre‐treatment inhibited lipopolysaccharide (LPS)‐induced overproduction of inflammation‐correlated cytokines such as nitric oxide (NO), prostaglandin E2 (PGE2), tumour necrosis factor α (TNF‐α) and interleukin 6 (IL‐6), and suppressed overexpression of inflammatory enzymes such as inducible nitric oxide synthase (iNOS) and cyclooxygenase 2 (COX‐2). Astilbin, on the other hand, prevented the LPS‐induced degradation of extracellular matrix (ECM) by down‐regulating MMP13 (matrix metalloproteinases 13) and ADAMTS5 (a disintegrin and metalloproteinase with thrombospondin motifs 5). Moreover, by inhibiting the formation of the TLR4/MD‐2/LPS complex, Astilbin blocked LPS‐induced activation of TLR4/NF‐κB signalling cascade. In vivo, Astilbin showed the chondro‐protective effect in the surgical‐induced OA mouse models. In conclusion, our findings provided evidence that develops Astilbin as a potential therapeutic drug for OA patients.